Histone deacetylase inhibitor valproic acid promotes the differentiation of human induced pluripotent stem cells into hepatocyte-like cells. - Yuki Kondo; Takahiro Iwao; Sachimi Yoshihashi; Kayo Mimori; Ruri Ogihara; Kiyoshi Nagata; Kouichi Kurose; Masayoshi Saito; Takuro Niwa; Takayoshi Suzuki; Naoki Miyata; Shigeru Ohmori; et al. (PLoS ONE, 2014)
In this study, we aimed to elucidate the effects and mechanism of action of valproic acid on hepatic differentiation from human induced pluripotent stem cell-derived hepatic progenitor cells. Human induced pluripotent stem cells were differentiated into endodermal cells in the presence of activin A and then into hepatic progenitor cells using dimethyl sulfoxide. Hepatic progenitor cells were matured in the presence of hepatocyte growth factor, oncostatin M, and dexamethasone with valproic acid that was added during the maturation process. After 25 days of differentiation, cells expressed hepatic marker genes and drug-metabolizing enzymes and exhibited drug-metabolizing enzyme activities. These expression levels and activities were increased by treatment with valproic acid, the timing and duration of which were important parameters to promote differentiation from human induced pluripotent stem cell-derived hepatic progenitor cells into hepatocytes. Valproic acid inhibited histone deacetylase activity during differentiation of human induced pluripotent stem cells, and other histone deacetylase inhibitors also enhanced differentiation into hepatocytes. In conclusion, histone deacetylase inhibitors such as valproic acid can be used to promote hepatic differentiation from human induced pluripotent stem cell-derived hepatic progenitor cells.